Land Conversion, Spatial Governance Failure, and Local Food Security Vulnerability: Evidence from Peri-Urban Malang, Indonesia - Ilham Nur Hanifan Maulana; Romy Hermawan (Universitas Kadiri, 2026)
Peri-urban agricultural land conversion presents a structural challenge to food security governance in rapidly urbanizing countries. In Indonesia, although Sustainable Food Agricultural Land (LP2B) is legally protected, conversion persists, questioning regulatory effectiveness. This study analyzes land conversion in peri-urban Malang, East Java, as a public policy problem by examining the relationship between governance performance and local food security outcomes from 2019–2025. A mixed-methods design integrates spatial land-use analysis, regression modeling of food availability (kcal/capita/day), and institutional assessment of policy implementation. Results indicate that 12.8% of protected agricultural land was converted during the study period, reflecting a significant implementation gap. Regression findings demonstrate a statistically significant association between cultivated land area and local food availability, while yield gains fail to compensate for land loss. Despite provincial production growth, local food availability declined toward adequacy thresholds. The study re-specifies food security as a governance and land protection problem rather than merely a production issue, underscoring the need for enforceable, incentive-aligned, and multi-level land governance instruments in peri-urban regions.